Model Kultur Tiga Dimensi Sel Punca Mesenkim: Kondisi Terkini dan Arah Pengembangan - Nurrahmah, Dewi; Nurhaliza, Febrianti (Insight of Biology, 2025)
Mesenchymal stem cells (MSCs) are multipotent progenitor cells with remarkable regenerative potential, widely studied for their application in tissue engineering and cell-based therapy. Conventional two-dimensional (2D) culture systems, although commonly used, fail to mimic the native three-dimensional (3D) microenvironment of MSCs, leading to limitations in proliferation, differentiation, and therapeutic efficacy. Recent advances in three-dimensional (3D) culture techniques have provided new perspectives on maintaining cell viability, enhancing paracrine activity, and promoting lineage-specific differentiation. This review article highlights the current state of MSC 3D culture models, including spheroid formation, scaffold-based systems, and perfusion bioreactors. Each approach offers unique advantages and challenges in terms of scalability, reproducibility, and clinical translation. Studies indicate that 3D culture not only enhances stemness characteristics but also improves the secretion of bioactive molecules, contributing to better in vivo therapeutic outcomes, such as angiogenesis, anti-inflammation, and tissue regeneration. Furthermore, this article discusses the future directions of MSC 3D culture, particularly the integration of biomaterial innovations, 3D bioprinting, and molecular approaches to optimize culture conditions. The establishment of standardized protocols aligned with Good Manufacturing Practice (GMP) is crucial for advancing MSC-based therapies toward clinical applications. Overall, MSC 3D culture models represent a promising frontier in regenerative medicine, bridging the gap between in vitro studies and clinical translation.